Status of Vitamin D and its Association with Stroke Risk Factors in Patients with Acute Ischemic Stroke in a Tertiary Care Hospital - Lekhjung Thapa; Baburam Pokhrel; Asis Shrestha; Manohar Pradhan; Tirtha Raj Bhandari; Shakti Shrestha; Ramesh Sharma Poudel; Raju Poudel (Journal of Nepal Medical Association, 2014)
Introduction: Vitamin D deficiency has been associated with many neurological illnesses. The status of Vitamin D in Nepalese ischemic stroke patients is still unknown. This study aims to assess the status of vitamin D and its association with stroke risk factors in patients with acute ischemic stroke from Central Nepal.